SMEs strategy and scale constraints impact on agri-food supply chain collaboration and firm performance - Zaridis, A.; Vlachos, I.; Bourlakis, Michael (Taylor and Francis, 2020)
This study examined the impact of collaboration in agri-food supply chains on firm performance and the moderating role of scale constraints and firm strategy. Collaboration was measured by three constructs: horizontal collaboration, vertical collaboration, and customer engagement and SME performance with three variables: growth, value for money and innovativeness. Two strategies were evaluated: price strategy and quality strategy. Three types of scale constraints were assessed: financial, efficiency, and innovation. A survey of 504 agri-SMEs was conducted to test the research hypotheses developed according to the resource based view. Data analysis included a moderated hierarchical analysis. The results show that supply chain collaboration impacts positively on agri-SME performance, whilst it is partially accepted that scale constraints moderate the supply chain collaboration-SME performance relationship. The findings show that SME strategy moderates the supply chain collaboration-SME performance relationship. This study provides evidence that agri-SMEs can strategize their supply chain collaborations by removing scale constraints. When supply chain collaborations help SMEs to overcome financial, efficiency or innovation constraints, then SMEs’ performance improves. Second, this study contributes to the understanding of dynamic capabilities in SMEs using the extended resource based view, which has been overlooked by prior studies.
Keywords: Agri-SMEs; supply chain collaboration; firm performance; strategy; scale constraints; survey